The Role of Learning and Communication Technologies in Online Courses’ Design and Delivery: A Cross-National Study of Faculty Perceptions and Practices - Meletiou-Mavrotheris, Maria; Mavrou, Katerina; Rebelo, Piedade Vaz (Frontiers in Education, 2021)
This article presents the results of a study, conducted within the scope of the EU-funded project RELOBIE: Reusable Learning Objects in Education, which investigated faculty perceptions and practices regarding the educational use of contemporary and emerging technologies. A cross-national, in-depth online survey of n=171 faculty members in the four partner countries (Estonia, Cyprus, Norway, Portugal) took place. Seventy-six (n=76; 44.4%) of these faculty members taught courses which were either offered at-distance (no face-to-face component), or involved a significant online component (blended courses). The study gained some useful insights into online instructors’ perceptions, motivations, and experiences regarding the instructional use of digital videos and other technologies (e.g. subject-specific software, collaboration tools, games, simulations, virtual labs). It also shed some light into both facilitating and inhibiting factors to the effective integration of learning and communication technologies into online courses’ design and delivery.